Contemporary Qur’anic Studies and Exegesis: A Comparative Epistemological Analysis of Non-Exegetical Works - Muhamad Muhamad; Edwin Rewira; Tegar Brian Baskoro (JURNAL ISLAM NUSANTARA, 2025)
This study aims to examine the epistemological characteristics, validity, and typologies of Qur’anic interpretations produced by non-mufassir intellectuals in contemporary Indonesia. Recent studies show that the growing involvement of scientists and non-traditional scholars in Qur’anic interpretation has expanded interdisciplinary engagement but also raised concerns regarding interpretive authority and methodological legitimacy. The tension between classical tafsir standards and modern scientific approaches necessitates a critical evaluative framework grounded in Qur’anic hermeneutics. This research employs a qualitative Systematic Literature Review (SLR) design to map, evaluate, and synthesize non-tafsir works produced by selected non-mufassir intellectuals. Data were analyzed using comparative and content analysis through the lenses of ma‘na cum maghza, maqaṣidi tafsir, and the integration interconnection paradigm. The findings reveal that interpretive validity is primarily determined by scholarly capacity and methodological awareness rather than formal religious status. Second, non-mufassir interpretations fall into five epistemological typologies: apologetic, confirmatory, heuristic, critical, and collaborative-integrative, with varying degrees of credibility. Third, Qur’an science integration is methodologically sound only when grounded in equitable interdisciplinary dialogue, respect for historical meaning, and maqaṣid-oriented objectives. This study contributes an evaluative epistemological framework for contemporary tafsir studies and recommends strengthening methodological discipline and academic validation in future interdisciplinary interpretations.